COMPARISON OF PAYMENTS FOR ACCESS TO AND USE OF RAILWAY INFRASTRUCTURE AND SELECTED SERVICE FACILITIES AT ŽSR FROM 01.01.2019 (Perner's Contacts, 2018)
The contribution briefly focuses on a new charging system for access to and use of railway infrastructure and service equipment at the ŽSR, which will enter into force on January 1, 2019 and analyzes the price comparisons with the valid system that applied in the period 1.1.2011 - 31.12.2018. The contribution focuses on payments for the minimum access package (so-called track-side payments) and payments for access to selected service facilities - passenger and freight stations.
Keywords: rail network, comparison, fee, service equipment